2020
DOI: 10.1002/hep4.1567
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Patient‐Reported Outcomes in Primary Biliary Cholangitis and Primary Sclerosing Cholangitis

Abstract: Primary biliary cholangitis (PBC) and primary sclerosing cholangitis (PSC) are associated with decreased health-related quality of life and debilitating symptoms. These experiences can be defined as patient-reported outcome (PRO) concepts and measured using PRO instruments. We identified all PRO concepts and instruments used in the PBC and PSC literature. This systematic review identified PBC and/or PSC studies from January 1, 1990, to May 6, 2019, that measured at least one PRO concept. Study population, desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 37 publications
2
9
0
Order By: Relevance
“…188,[454][455][456] Symptoms are among the top concerns of people with PSC; according to a recent systematic review, the 5 most common symptoms in PSC are pruritus, fatigue, abdominal pain, diarrhoea and nausea/vomiting. 457 In particular, pruritus is associated with reduced social and physical functioning as well as general and mental health, and depression is significantly worse in patients with severe pruritus. 458 The mental component scores appear to be influenced by lifestyle modifications secondary to liver disease, social interactions and loneliness, and were worse in patients with more severe itching, shorter IBD duration and depression.…”
Section: How Can Wellbeing Of People With Psc Be Optimised?mentioning
confidence: 99%
See 1 more Smart Citation
“…188,[454][455][456] Symptoms are among the top concerns of people with PSC; according to a recent systematic review, the 5 most common symptoms in PSC are pruritus, fatigue, abdominal pain, diarrhoea and nausea/vomiting. 457 In particular, pruritus is associated with reduced social and physical functioning as well as general and mental health, and depression is significantly worse in patients with severe pruritus. 458 The mental component scores appear to be influenced by lifestyle modifications secondary to liver disease, social interactions and loneliness, and were worse in patients with more severe itching, shorter IBD duration and depression.…”
Section: How Can Wellbeing Of People With Psc Be Optimised?mentioning
confidence: 99%
“…The use of patient-reported outcome measures (PROMS) in routine clinical practice may help to guide the implementation of a more patient-centred approach to care in PSC. 457,459 By using PROMS in the clinical setting, we expect to i) improve communication between patients and clinicians, ii) enhance patient engagement in his/her care and improve adherence to treatment, iii) improve monitoring and reporting of symptoms and iv) aid patient recall of issues to be discussed during the clinic appointment. 459 Although it is expected that the use of PROMS in clinical settings will be very beneficial, well-validated, disease-specific instruments are scarce in PSC.…”
Section: How Can Wellbeing Of People With Psc Be Optimised?mentioning
confidence: 99%
“…Each assessment tool should be validated not to compromise the quality of research. In a systematic review by Kim et al [ 22 ], the authors found that, between 1990 and 2019, patient reported outcomes in PBC had been mostly assessed with unlabelled, nonspecific versions of numeric ratings or Likert scales and that fatigue has been measured with over ten different instruments although ideally, the use of questionnaires should be standardised to allow comparison.…”
Section: Assessment Of Fatiguementioning
confidence: 99%
“…Recent data from the UK-AIH national cohort study indicate quality of life is significantly impaired in AIH patients, as is particularly associated with steroid use (177). A recently published systematic review of patient reported outcomes in studies of PBC and PSC concluded that although the use of patient reported outcomes has increased over time, many are nonspecific and unvalidated (178). This underscores the importance in developing and evaluating relevant patient reported outcomes in clinical trials of novel therapeutics alongside clinical efficacy signals.…”
Section: Current Research Gaps and Potential Developments In The Fieldmentioning
confidence: 99%